DETERMINATION OF TOTAL PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY OF ETHANOL EXTRACT MATOA LEAVES (Pometia pinnata) BY SOXHLET EXTRACTION - Tisa Mandala Sari; Hazli Nurdin; Febti Nengsih; Miftahur Rahmi (DIVERSITAS HAYATI, 2025)
The matoa plant (Pometia pinnata) is one of the medicinal plants frequently used for traditional medicine by the Indonesian community. This research aims to determine the total phenolic content and antioxidant activity of matoa leaf extract obtained through the soxhlet extraction method using 70% ethanol as a solvent. The total phenolic content of the matoa leaf ethanol extract was analyzed using the Folin-Ciocalteu method, and the antioxidant activity was tested using the DPPH method with gallic acid as a comparison compound, measured using a UV-Vis Spectrophotometer. The total phenolic content of the ethanol extract from the soxhlet-extracted matoa leaves at the maximum absorption wavelength of 762 nm was found to be 13.98% b/b. The antioxidant activity test of gallic acid yielded an IC50 of 7.922 µg/mL, and the antioxidant activity of the ethanol extract from the soxhlet-extracted matoa leaves at the maximum absorption wavelength of 521 nm yielded an IC50 of 112.854 µg/mL. Based on the IC50 values, it can be concluded that the antioxidant activity of the ethanol extract from the soxhlet-extracted matoa leaves falls into the moderate category, specifically in the range of 100-150 µg/mL. The equivalence of the antioxidant activity of the matoa leaf ethanol extract to gallic acid is 1:14.2456 mg, meaning that 1 mg of gallic acid is equivalent to 14.2456 mg of matoa leaf ethanol extract.